Pengaruh Penyiraman terhadap Kecepatan Berkecambah dan Daya Kecambah Benih Kelapa Dalam - Manambangtua, Alfred Pahala; Hidayat, Toni S (Seminar Nasional Lahan Suboptimal, 2022)
Manambangtua AP, Hidayat TS. 2022. The effect of watering on the germination speed and the germination of tall coconut seeds. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 736-741. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).At this time the government is intensifying coconut planting to be developed in the community, so good quality seeds are needed. To get quality seeds, it is necessary to pay attention to handling the provision of good and correct seeds, so that good quality seeds are obtained that have the criteria uniform germination speed and high germination rate. Availability of water is an absolute thing in the provision of seeds. At the beginning of nursery, farmers paid less attention to watering the seeds, they think that the seeds in the nursery do not need a lot of water. Water plays an important role in plant growth however it is necessary to know whether water also plays a role in the initial growth of coconut seeds in the nursery. This study aimed to determine the role of water for coconut seeds in the early growth in the nursery. The research was carried out at the Balitpalma Experimental Garden, Mapanget, North Sulawesi. Held in August 2019 – October 2019. The study used two treatments consisting of: a) watered coconut seeds and b) unwatered coconut seeds, each treatment contained 75 plants so that 150 coconut seeds were used, then the independent t-test was conducted. The watering treatment showed no significant difference in the speed of germination. The germination rate showed a significant difference, a high value was obtained in the watering treatment. The watering treatment showed that the results were not significantly different from the speed of germination, but significantly different to the germination rate.